Knowledge is Power: Module-level Sensing for Runtime Optimisation - Davis,JJ; Hung,E; Levine,J; Stott,E; Cheung,PYK; Constantinides,GA (ACM, 2016)
We propose the compile-time instrumentation of coexisting modules---IP blocks, accelerators, etc.---implemented in FPGAs. The efficient mapping of tasks to execution units can then be achieved, for power and/or timing performance, by tracking dynamic power consumption and/or timing slack online at module-level granularity. Our proposed instrumentation is transparent, thereby not affecting circuit functionality. Power and timing overheads have proven to be small and tend to be outweighed by the exposed runtime benefits.